Conjugated Linoleic Acid Production by Bifidobacteria: Screening, Kinetic, and Composition. (27th June 2016) - Raimondi, Stefano; Amaretti, Alberto; Leonardi, Alan; Quartieri, Andrea; Gozzoli, Caterina; Rossi, Maddalena
Abstract : Conjugated linoleic acids (CLA) are positional and geometric isomers of linoleic acid involved in a number of health aspects. In humans, CLA production is performed by gut microbiota, including some species of potential probiotic bifidobacteria. 128 strains of 31 Bifidobacterium species were screened with a spectrophotometric assay to identify novel CLA producers. Most species were nonproducers, while producers belonged to B. breve and B. pseudocatenulatum . GC-MS revealed that CLA producer strains yielded 9 cis, 11 trans -CLA and 9 trans, 11 trans -CLA, without any production of other isomers. Hydroxylated forms of LA were absent in producer strains, suggesting that the myosin-cross-reactive antigen (MCRA) protein that exerts hydratase activity is not involved in LA isomerization. Moreover, both CLA producer and nonproducer species bear a MCRA homologue. The strain B. breve WC 0421 was the best CLA producer, converting LA into 68.8% 9 cis, 11 trans -CLA and 25.1% 9 trans, 11 trans -CLA. Production occurred mostly during the lag and the exponential phase. For the first time, production and incorporation of CLA in biomass were assessed. B. breve WC 0421 stored CLA in the form of free fatty acids, without changing the composition of the esterified fatty acids, which mainly occurred in the plasmatic membrane.